Study on combustion of aluminum powder mixed with sodium borohydride at low starting temperature in steam atmosphere. Issue 17 (2nd September 2021) - Shi, Wei; Yang, Weijuan; Du, Longjin; Liu, Jianzhong; Zhou, Junhu
ABSTRACT: The hydrogen generation performance of the mixture of aluminum powder and sodium borohydride was investigated experimentally in steam atmosphere to reveal the promotion effects and mechanism of sodium borohydride to aluminum powder. Sodium borohydride is used as both heat generating agent and hydrogen generating agent simultaneously. The energy and hydrogen release characteristics were revealed through a series of experiments by a homemade reactor, and the starting temperature and addition rate of NaBH4 were concentrated on. The dynamic process of sample-water reactions was analyzed by temperatures and pressure in the reactor, as well as H2 flow rate. The results showed that the addition of sodium borohydride can significantly improve the H2 generation efficiency of aluminum powder with steam and the start-off temperature of Al-NaBH4 mixture can be reduced to 260°C for continuous H2 generation with water vapor. The reacted ratio of aluminum powder was detected to be about 90%. The products were detected by SEM and XRD, which implied that new products, NaAl23 O35 and Al5 O6 (BO3 ), appears because of the addition of sodium borohydride.